1992
DOI: 10.1111/j.1348-0421.1992.tb02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous Ingestion of Staphylococcus aureus Organisms by Murine Fibroblasts In Vitro

Abstract: A conspicuous adhesion of Staphylococcus aureus organisms to murine cutaneous fibroblasts and NIH/ 3T3 cells cultured in vitro and subsequent ingestion of S. aureus organisms by these fibroblasts are described.In the present experimental system, only fibroblasts-adhering S. aureus organisms were efficiently ingested by fibroblasts unlike S. epidermidis and S. saprophyticus. These findings might suggest a correlation between the pathogenesis of S. aureus and its intracellular localization in non-professional ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
(12 reference statements)
0
25
0
Order By: Relevance
“…Bacteremia, inflammatory parameters and oxidative stress related parameters were observed to assess the effective duration of nanoconjugated vancomycin against VSSA and VRSA infection. Results: The result revealed that in vivo VSSA and VRSA infection developed after 5 days of challenge by elevating the NO generation in lymphocyte and serum inflammatory markers. Administration with nanoconjugated vancomycin to VSSA and VRSA infected group at a dose of 100 mg/kg bw/day and 500 mg/kg bw/day, respectively, for successive 10 days eliminated bacterimia, decreased NO generation in lymphocyte, serum inflammatory markers and increased antioxidant enzyme status.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Bacteremia, inflammatory parameters and oxidative stress related parameters were observed to assess the effective duration of nanoconjugated vancomycin against VSSA and VRSA infection. Results: The result revealed that in vivo VSSA and VRSA infection developed after 5 days of challenge by elevating the NO generation in lymphocyte and serum inflammatory markers. Administration with nanoconjugated vancomycin to VSSA and VRSA infected group at a dose of 100 mg/kg bw/day and 500 mg/kg bw/day, respectively, for successive 10 days eliminated bacterimia, decreased NO generation in lymphocyte, serum inflammatory markers and increased antioxidant enzyme status.…”
Section: Introductionmentioning
confidence: 96%
“…Bacteremia and inflammatory parameters were observed to evaluate the duration for development of VSSA and VRSA infection. 100 mg/kg bw/day and 500 mg/kg bw/day nanoconjugated vancomycin were administrated to VSSA and VRSA infected group for 5 days. Bacteremia, inflammatory parameters and oxidative stress related parameters were tested to observe the effective dose of nanoconjugated vancomycin against VSSA and VRSA infection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This staphylococcal localization suggests a close connection between fibroblasts and staphylococcal growth. Indeed, there are many reports on the specific affinity between S. aureus and extracellular matrix produced by fibroblasts (3,6,7,12) or the fibroblast cell itself including the ingestion of the cocci (5,11). Normal connective tissue, however, does not permit staphylococcal growth with a small inoculum.…”
mentioning
confidence: 99%